INOVASI METODE PRODUKSI UNTUK OPTIMALISASI USAHA UKM BATIK BIRU LANCOR, KABUPATEN PROBOLINGGO - Widayanto Mutinda Teguh; Koeshardjono R Hery; Abdillah Hartawan; Chantika Amelia Najwa; Nirbaya Nanda Puti Aptha (Universitas Mataram, 2023)
The existence of SMEs as a driving force for the economy is no longer in doubt, but there are still many obstacles that cannot be overcome. UKM Batik Biru Lancor is one of the SME that has the potential to develop but still faces problems in the areas of quality and production capacity that cannot yet meet market demand. This community service activity aims to provide solutions to partners in overcoming obstacles to developing their business. The method applied is by designing equipment in the form of a batik drawing table, using a gas batik stove and providing training to the SME. The results obtained by partners are an increase in employee skills and additional production support equipment so that the quality and quantity of production increases. In this way, community service activities as one of the obligations of the Tridharma of Higher Education have achieved the target of solving partners' problems in developing their business and making a greater contribution to the surrounding economy.